Childhood IQ in relation to later psychiatric disorder - G. David Batty; Erik Lykke Mortensen; Merete Osler (2005)
Studies examining the relationship between early-life IQ and the risk of subsequent psychiatric disorder in adulthood are scarce. In the present investigation, the childhood IQ scores of 7022 singleton-born Danish males were linked to psychiatric hospital discharge records in adulthood. IQ scores were inversely related to the risk of total psychiatric illness, with the highest levels apparent in the lowest scoring IQ group (HRlowest quintile v. highest=1.70, 95% CI 1.34-2.14). Adjusting for paternal occupational social class and birth weight had only a small attenuating effect. Low childhood IQ may have an aetiological role in the development of adult total psychiatric disorder.